Eco-socialism and the political ecology of forest conservation in the Greater Khingan Range, China. (March 2022) - Zhu, Liyuan; Lo, Kevin
Abstract: State-owned forestry enterprises (SOFEs) in China, established during the Maoist era for forest exploitation, have undergone significant reorganization under the Natural Forest Conservation Program (NFCP). In this study, drawing on the perspectives of political ecology and a case study from a SOFE in the Greater Khingan Range in northeast China, we develop an eco-socialist perspective to understand this particular approach to forest conservation. The concept of eco-socialism is mobilized to describe how, as a form of all-encompassing social organization with overwhelming political, social, and economic power in the forestry regions, the eco-restructuring of SOFEs is key to the success of forest conservation. Four eco-restructuring processes have been identified: (1) declining timber sales and increasing central subsidies; (2) restructuring of work-units; (3) creating redundancies; and (4) developing new sustainable economic activities. Furthermore, these eco-restructuring processes, both mandated and supported by the central government, have a significant impact on state-society relationship. While the resources given by the central government allow SOFEs to maintain a stable relationship with some workers by providing them a relatively stable livelihood, the laid-off workers are the major victims of the process, as they suffer from loss of income, economic stability, and social self-esteem. This study enriches the literature by incorporating eco-socialist governmentality into the political ecology of forest conservation and illustrating how the political ecology perspective can be a powerful tool in the collective effort to craft sustainable and socially just futures in China.